2021
DOI: 10.3389/fpsyg.2021.637569
|View full text |Cite
|
Sign up to set email alerts
|

Mothers as Home DJs: Recorded Music and Young Children’s Well-Being During the COVID-19 Pandemic

Abstract: As the COVID-19 pandemic continues to disrupt our lives in unimagined ways, families are reinventing daily rituals, and this is likely true for musical rituals. This study explored how parents with young children used recorded music in their everyday lives during the pandemic. Mothers (N = 19) of child(ren) aged 18 months to 5 years living in the United States played the role of home DJ over a period of one week by strategically crafting the sonic home environment, based on resources provided by the authors, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 52 publications
2
19
0
Order By: Relevance
“…While most people experienced equally strong emotions in response to music during lockdown compared to before, increases were slightly more frequent than decreases-but this was also the case for non-music-induced emotions (Ziv & Hollander-Shabtai, 2021). Musical activities in children increased during lockdown, and parents used music significantly more for emotion regulation and for connecting socially with their offspring (Cho & Ilari, 2021;Ribeiro et al, 2021a;Steinberg et al, 2021). Taken together, these results strongly confirm pre-pandemic findings that music listening is capable of effectively enhancing wellbeing (Randall & Rickard, 2017;Saarikallio, 2011).…”
Section: Coping Efficacysupporting
confidence: 69%
“…While most people experienced equally strong emotions in response to music during lockdown compared to before, increases were slightly more frequent than decreases-but this was also the case for non-music-induced emotions (Ziv & Hollander-Shabtai, 2021). Musical activities in children increased during lockdown, and parents used music significantly more for emotion regulation and for connecting socially with their offspring (Cho & Ilari, 2021;Ribeiro et al, 2021a;Steinberg et al, 2021). Taken together, these results strongly confirm pre-pandemic findings that music listening is capable of effectively enhancing wellbeing (Randall & Rickard, 2017;Saarikallio, 2011).…”
Section: Coping Efficacysupporting
confidence: 69%
“…Despite the methodological limitations noted, our research adds to a body of literature documenting adult-child musical experiences during COVID-19. Caregivers of young children have turned to musical engagement frequently during the pandemic, using musical recordings and joint musical activities to connect with their children and help children regulate their emotions (Cho & Ilari, 2021;Steinberg et al, 2021). Similarly, secondary music educators in Australia prioritized building relationships with their students through music (de Bruin, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The increase in "play with children" seems to reflect that the adults had to spend a long time taking care of children during school closures. Researchers have reported that parents increasingly use music to moderate and enhance children's emotions during SiP (Cho and Ilari, 2021;Ribeiro et al, 2021a;Steinberg et al, 2021). We presume that our results reflect the behavior of caregivers.…”
Section: Stressmentioning
confidence: 56%